Chiral Flavonoids as Antitumor Agents - Cláudia Pinto; Honorina Cidade; Madalena Pinto; Maria Elizabeth Tiritan (MDPI AG, 2021)
Flavonoids are a group of natural products with a great structural diversity, widely distributed in plant kingdom. They play an important role in plant growth, development and defense against aggressors. Flavonoids show a huge variety of biological activities such as antioxidant, anti-inflammatory, anti-mutagenic, antimicrobial and antitumor, being able to modulate a large diversity of cellular enzymatic activities. Among natural flavonoids, some classes comprise chiral molecules including flavanones, flavan-3-ols, isoflavanones, and rotenoids, which have one or more stereogenic centers. Interestingly, in some cases, individual compounds of enantiomeric pairs have shown different antitumor activity. In nature, these compounds are mainly biosynthesized as pure enantiomers. Nevertheless, they are often isolated as racemates, being necessary to carry out their chiral separation to perform enantioselectivity studies. Synthetic chiral flavonoids with promising antitumor activity have also been obtained using diverse synthetic approaches. In fact, several new chiral bioactive flavonoids have been synthesized by enantioselective synthesis. Particularly, flavopiridol was the first cyclin-dependent kinase (CDK) inhibitor which entered clinical trials. The chiral pool approaches using amino acid as chiral building blocks have also been reported to achieve small libraries of chrysin derivatives with more potent in vitro growth inhibitory effect than chrysin, reinforcing the importance of the introduction of chiral moieties to improve antitumor activity. In this work, a literature review of natural and synthetic chiral flavonoids with antitumor activity is reported for the first time.